RUMAH EBANG SEBAGAI TEMPAT, SUMBER DAN MEDIA PEMBELAJARAN GEOMETRI SD DI LUAR KELAS BERBASIS ETNOMATEMATIKA - Gregorius Sebo Bito; Fredy Fredy (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Mathematics learning can be carried out outside the classroom and the material can come from things that are close to students' daily lives. There needs to be a place, resources, and learning media to bridge students' cultural knowledge with mathematics material in schools. One of them is the student's knowledge of the Ebang house. This study aims to describe the Ebang house in Lembata and its potential as a place, source, and medium for learning elementary school geometry. This research is qualitative research. The research object is the Ebang house of the Kedang community on Lembata Island. The instrument used is data documentation in the form of pictures of traditional houses and interview data. The results of the study show that there are many geometric elements in the Ebang house. These geometric elements include plane shapes (triangles, quadrilaterals, polygons, trapezoids and circles) and spatial shapes (beams, pyramids, prisms, cubes, needles, and spheres. As a place and source of learning outside the classroom, students can observe directly the shapes geometric shapes contained in the Ebang house and its parts. In addition, the Ebang house can be a concrete medium to assist teachers in explaining geometric concepts to students. Planning for outdoor learning has the potential to make the Ebang house a good place for learning geometry because of the availability of materials and elementary school geometry learning media.